Studi Teologis Pentingnya Pemberitaan Firman Berdasarkan Kitab 2 Timotius 4:2-3 - Sariyanto, Sariyanto (Ritornera - Jurnal Teologi Pentakosta Indonesia, 2023)
In the midst of the times, the church is faced with the emergence of various heresies or false teachings. Where false teaching leads to heresy and can damage the Christian faith. Similarly, false teaching is feared to lead to a decline in faith, and spiritual difficulty growing. The role of the preacher of the word is very important and determines the growth of faith, if the preacher does not prepare himself, and does not understand the truth of God will be very detrimental to the spirituality of the church. The purpose of this study is to find a theological basis for the importance of preaching the word to build up Christians, and maintain the faith of the church. The method used in this study is a qualitative method with a hermenutic-exegesis approach. The conclusion of this study is this: the teaching of God's Word is the responsibility of God's servants, and must be preached correctly. God's Word has the power to convict sin, purify humanity, lead to new birth, and to grow the Christian faith. God's Word that is preached truly can grow the spirituality of the church, and can counter heresy.AbstrakDi tengah perkembangan zaman, gereja diperhadapkan dengan munculnya berbagai ajaran sesat atau ajaran palsu. Dimana pengajaran palsu tersebut menuju kesesatan dan dapat merusak iman Kristen. Demikian pula pengajaran palsu dikhawatirkan akan mengakibatkan kemunduran iman, dan rohani sulit bertumbuh. Peran pemberita firman sangatlah penting dan menentukan pertumbuhan iman, bila pemberita tidak mempersiapkan diri, dan tidak memahami kebenaran Allah akan sangat merugikan kerohanian jemaat. Tujuan dari penelitian ini untuk menemukan dasar teologis mengenai pentingnya pemberitaan firman untuk membangun orang Kristen, dan memelihara iman jemaat. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan hermenutik-eksegesis. Kesimpulan dari penelitian ini adalah: pengajaran Firman Allah menjadi tanggung jawab para hamba Tuhan, dan harus diberitakan dengan benar. Firman Allah memiliki kuasa untuk menginsafkan akan dosa, menyucikan manuisa, membawa kepada kelahiran baru, menumbuhkan iman orang Kristen. Firman Allah yang diberitakan secara sungguh dapat menumbuhkan kerohanian jemaat, dan dapat melawan ajaran sesat.